If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -6x = 6(x + -5) + -6 Reorder the terms: 24 + -6x = 6(-5 + x) + -6 24 + -6x = (-5 * 6 + x * 6) + -6 24 + -6x = (-30 + 6x) + -6 Reorder the terms: 24 + -6x = -30 + -6 + 6x Combine like terms: -30 + -6 = -36 24 + -6x = -36 + 6x Solving 24 + -6x = -36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 24 + -6x + -6x = -36 + 6x + -6x Combine like terms: -6x + -6x = -12x 24 + -12x = -36 + 6x + -6x Combine like terms: 6x + -6x = 0 24 + -12x = -36 + 0 24 + -12x = -36 Add '-24' to each side of the equation. 24 + -24 + -12x = -36 + -24 Combine like terms: 24 + -24 = 0 0 + -12x = -36 + -24 -12x = -36 + -24 Combine like terms: -36 + -24 = -60 -12x = -60 Divide each side by '-12'. x = 5 Simplifying x = 5
| 2/b-4 | | Y/4/5=20 | | 12x+12+12x=90 | | c^2+35c=0 | | -1-6x=9-2 | | 3n-5=/ | | 9t+4=-14E | | 12r^2+7rs-10s^2= | | 1-2/3x=-15 | | 3(k-8)-(k+5)=23 | | -20x^2+180=0 | | 5-x=9x+5 | | (3z+5)(z+3)=7 | | 12+4c=6-(19+13) | | 1=2/3=-15 | | 12+12x+12x=90 | | 5+(n+3)+4n= | | 2x^2-11x+17=0 | | y=-2(8)+7 | | 6x-8=-6 | | -7x-9+6x=-15 | | -7x-9+6x=-15 | | 3/8y=3 | | (-4x^4/3x^7)^-2 | | 67=4y+11 | | 12+12x+12=90 | | (-8x^3)+72x=0 | | 12-8t= | | 0.005x^2+x+200=0 | | 3x+9+8x+11+5x+-8=180 | | 8x+10+8x=90 | | 12r^2+7rs-10s^2=12r^2-8rs+15rs-10s^2 |